The modern manual of authoritarian leadership. Issue 5 (4th July 2022) - Patapan, Haig
ABSTRACT: The rise of modern authoritarianism is distinguished by its increasing sophistication in the techniques of authoritarian rule. Is it possible to comprehend these modern authoritarian techniques within a larger framework that accounts for their theoretical provenance, interrelationship and efficacy? This article argues that the nature and structure of the modern state has shaped the form and expression of authoritarian rule. More specifically, it shows how Thomas Hobbes, the influential theoretical founder of the modern state, can account for the modern "manual" of authoritarian leadership, with its distinctive use of rule of law and constitutions, voting and elections, and a free marketplace as means to enhance power and consolidate rule. Understanding the theoretical foundations of this modern manual is valuable for providing new insights into the efficacy of these techniques and thereby the dangers posed by modern authoritarians and the means to counter their threat.